Oral cavity infection: an adverse effect after the treatment of oral cancer in aged individuals (Journal of Applied Oral Science, 2014)
Objective: The immune compromised patients after treatment of oral cancer may have a chance of infection by drug-resistant opportunistic microbes. We investigated the occurrence of opportunistic microorganisms in aged individuals receiving follow-up examinations after treatment of oral cancer in China. Material and Methods: These patients were used as test group and the respective age grouped healthy individuals as control group. In this study, the oral cavity microorganisms such as bacteria and yeast were taken for the analysis. After the screening of representative microorganisms, their aptitude of pervasiveness against drugs was studied. Here, we used antimicrobial agents which are common in clinical practice. We also performed studies to investigate the presence of toxin genes in methicillin-resistant S. aureus (MRSA). Results: The results indicate that the prevalence of drug-resistant microbes was more pronounced in oral cancer patients after initial treatment above 70 years old. The oxacillin resistance of S. aureus isolate confirms that the prevalence of MRSA is increasing in accordance to age-factor and immune compromise in elderly patients. Conclusions: This study reveals the occurrence of drug-resistant opportunistic microorganisms in oral cavity after treatment for oral cancer in aged individuals. Special attention should be directed to MRSA during the treatment of oral cancer, and to realize the fact of immune compromise in elderly patients.